Viabilidade econômica do cultivo da alface crespa em monocultura e em consórcio com pepino - Silva, Gilson Silverio Da [UNESP]; Rezende, Bráulio Luciano Alves; Cecílio Filho, Arthur Bernardes [UNESP]; Barros Júnior, Aurélio Paes; Martins, Maria Inez Espagnoli Geraldo [UNESP]; Porto, Diego Resende De Queirós [UNESP] (Editora da Universidade Federal de Lavras, 2008)
The protected culture, among other advantages, made possible to diminish the seasoning in offers and to improve the quality of vegetables. However, one consists in technology of high cost, that it may be attenuated with the increase in the efficiency of the use of the protected area, proportionated for the intercropping. The experiment was carried out at greenhouse at UNESP, Jaboticabal-SP, in the period of August and November of 2005, with the aim of evaluating the operational cost (COT) and the profitability of the crisphead lettuce Verônica (Lactuca sativa L.) in monoculture and in intercropping with the Japanese cucumber Hokushin (Cucumis sativus L.), in protected environment. The main cost items analyzed were the operational cost, the agricultural amendments and the materials cost. For the crisphead lettuce in monoculture and in intercropping, the COT was R$ 696,37 and R$ 295,06/614,4 m² respectively and the productivity was 822.53 and 890.78 kg/614,4 m². In monoculture and in intercropping the gross incomes were R$ 489,93 and R$ 452,39/614,4 m² respectively. It was verified a loss of R$ 206,44/614,4 m² in the crisphead lettuce monoculture and an operational profit of R$ 157,33/614,4 m² in protected environment when in intercropping with cucumber.

O cultivo protegido, entre outras vantagens, possibilita diminuir a sazonalidade na oferta e melhorar a qualidade das hortaliças. No entanto, constitui-se em tecnologia de elevado custo, que pode ser atenuado com o aumento na eficiência do uso da área protegida, proporcionado pelo cultivo consorciado. O trabalho foi realizado em casa de vegetação, na Unesp, Jaboticabal, SP, no período de agosto e novembro de 2005, e objetivou-se verificar o custo operacional total (COT) e a rentabilidade líquida da alface crespa 'Verônica' (Lactuca sativa L.) em monocultura e consorciada com pepino japonês 'Hokushin' (Cucumis sativus L.), em ambiente protegido. Os principais itens de custos estimados foram os referentes à operações, insumos e materiais. Para a alface crespa em monocultura e em consórcio, o COT foi de R$ 696,37 e R$ 295,06/614,4 m², e as produtividades de 890,78 e 822,53 kg/614,4 m², respectivamente em monocultura e em consórcio e as receitas brutas obtidas foram de R$ 489,93 e R$ 452,39/614,4 m². Em cultivo protegido, a monocultura de alface teve prejuízo de R$206,44/614,4 m², enquanto, em consórcio com pepino, a cultura da alface crespa 'Verônica' teve lucro operacional de R$ 157,33/614,4 m².
Economic viability of the crisphead lettuce culture in monoculture and intercropping with cucumber
Keywords: Lactuca sativa; Cucumis sativus; hand labor; greenhouse; production cost; Lactuca sativa; Cucumis sativus; mão-de-obra; casa de vegetação; custo de produção